THE CREATION OF UNCERTAIN TIME WORK AGREEMENT ALONG THE REFRESHMENT OF IRRELEVANT COMPANY REGULATIONS ON PT. MEGA BUANA INDAH - Edson Jonkarlo; Winsherly Tan (ConCEPt - Conference on Community Engagement Project, 2022)
Worker is an important position in the life of a country because it is a factor that determines the material and cultural success of the country itself. Therefore, it is necessary to adopt the best arrangements for various employment issues, workers rights to support work and a decent living. Law Number 13 concerning Manpower Year 2003 regulates various matters relating to the protection of workers, including the right to fair wages, leave rights including the right to legal certainty, and changes in the status of workers (contract workers) for a certain period of time. The reform of laws and regulations in the field of manpower aims to provide justice and protection for workers, as well as fulfill the mission of the 1945 Constitution, namely the achievement and social development of Indonesian society as a whole. The development of the Indonesian people as a whole, increasing the dignity, and entrepreneurial values ​​of the Indonesian nation, as well as realizing a prosperous, and materially and spiritually. The implementation of this Community Service uses the Advocacy method to assist partners (employers) in improving legal documents/property agreements. The results achieved in this Community Service are the draft of Permanent Employment Contract and draft of the Company Regulations after modernized.